The economics of the performing arts before and during the COVID-19 pandemic. Part 2: an investment approach to cultural enents - D. L. Morozova (Вестник университета)
The article demonstrates the possibilities of corporate governance methods and investment decision-making models for the cultural organizations and events (on the examples of federal theaters). Financial and investment analysis was applied in the study. The article discusses the hypothesis of the possibility of balancing budgets for new theatrical productions, taking the rehearsal period, premiere and running as a whole. The productions are not considered as deadweight losses, but are analysed as assets with risky returns. The results of the financial analysis of the staging activities of the leading theaters demonstrate their limited possibilities in balancing the budgets for new productions. The most popular performance (with an average ticket price above the market and a stable occupancy rate of over 90 %) requires at least 5–6 years of active running to recoup the initial investment. The author’s are expected to help the performing arts organizations to identify and assess losses during the pandemic crisis. The scientific novelty is to the approach to calculating and forecasting the return on production costs.